The oddly pedestrian life of christopher chaos (2023), volume 1 ebook - Brombal, Tate (The Oddly Pedestrian Life of Christopher Chaos (2023), 2024)
From the New York Times bestselling writers James Tynion IV and Tate Brombal (Something is Killing the Children and House of Slaughter) and the artist Isaac Goodhart (Victor and Nora: A Gotham Love Story) comes this LGBTQ+ horror-hero coming-of-age story that’s Invincible meets Doom Patrol.Meet teenage mad scientist Christopher Chaos. For all his life he knew he was different. His brilliant mind works in ways that defy logic and enable him to do things that push him beyond his peers. Unfortunately, these abilities have also caused great pain in his personal life—leading others to fear him and leaving Christopher with profound loneliness and guilt.Then one day something cracked. When the cute boy at high school turns out to be a deadly creature, Christopher finds himself in a world of monsters, heroes, and a cult of hunters out to kill them all.Tiny Onion Studios and Dark Horse Comics present a line of upcoming creator-owned work from the mind of James Tynion IV across a broad spectrum of his interests, from non-fiction supernatural encounters to high concept coming-of-age monster comics.Collects the Dark Horse Comics series The Oddly Pedestrian Life of Christopher Chaos #1–#6, featuring bonus process material and a ten-page prologue story never before seen in print.